2011
DOI: 10.1177/0883073811426501
|View full text |Cite
|
Sign up to set email alerts
|

Use of Complementary and Alternative Medicine by Males With Duchenne or Becker Muscular Dystrophy

Abstract: Use of complementary and alternative medicine by males with Duchenne or Becker muscular dystrophy was examined using interview reports from caregivers enrolled in the population-based Muscular Dystrophy Surveillance, Tracking, and Research Network. Of the 200 caregivers interviewed, 160 (80%) reported "ever" using complementary and alternative medicine for their affected children. Mind-body medicine (61.5%) was most frequently used, followed by biologically based practices (48.0%), manipulative and body-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…This helplessness and the lack of evidence-based alternatives leaves open a large market for non-evidence-based CAM use in patients with mitochondrial disease. Comparable rates of CAM use (∼80 %) have been reported in pediatric patients with Duchenne or Becker muscular dystrophy (Nabukera et al 2012). For patients with lysosomal storage disorders, the use of CAM reported in one single-center study was lower: C 8 %/A 45 % for type I Gaucher disease, C 50 %/A41 % of Fabry disease, and C 33 %/A 47 % of type B Niemann-Pick patients (Balwani et al 2009).…”
Section: Discussionmentioning
confidence: 93%
“…This helplessness and the lack of evidence-based alternatives leaves open a large market for non-evidence-based CAM use in patients with mitochondrial disease. Comparable rates of CAM use (∼80 %) have been reported in pediatric patients with Duchenne or Becker muscular dystrophy (Nabukera et al 2012). For patients with lysosomal storage disorders, the use of CAM reported in one single-center study was lower: C 8 %/A 45 % for type I Gaucher disease, C 50 %/A41 % of Fabry disease, and C 33 %/A 47 % of type B Niemann-Pick patients (Balwani et al 2009).…”
Section: Discussionmentioning
confidence: 93%
“…If symptoms occurred before the sixth birthday, disease was classified as early onset, otherwise it was classified as late onset. 16 The number of years since disease diagnosis was calculated as the difference between age at interview and age at diagnosis. If the male was deceased at the time of interview, the age at death was used instead of the age at interview.…”
Section: Methodsmentioning
confidence: 99%
“…A study using data from a population-based cohort of male patients with Duchenne or Becker muscular dystrophy identified by the Muscular Dystrophy Surveillance, Tracking, and Research Network (MD STAR net ) estimated that 80% of families used CAM for their children. 16 This analysis also evaluated the impact of care-giver characteristics on CAM use and observed caregivers who reported use of whole medical system therapies for their childrenwere more likely to have college education and a higher family income. 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from the MD STARnet were reviewed to determine frequency and types of use of complementary and alternative medical treatments and showed that 80 % of caregivers reported using complementary and alternative treatments at least once [42].…”
Section: Complementary and Alternative Treatmentsmentioning
confidence: 99%